The association of healthy eating index with periodontitis in National Health and Nutrition Examination Study 2011–2012 - Li, Xin-yu; Liu, Hui; Zhang, Lu-yu; Yang, Xi-tao (Frontiers in Nutrition, 2022)
Aim Periodontitis is a chronic inflammatory disorder caused by periodontopathic bacteria that causes inflammation of the supporting tissues around teeth. Previous studies have found that daily dietary nutritional intake can influence the development of periodontal disease. However, research on the Healthy Eating Index’s involvement in periodontitis is limited. The purpose of this study was to look at the link between the Healthy Eating Index and periodontitis. Methods and design We examined data from the National Health and Nutrition Examination Study (NHANES), a nationally representative survey that was performed in 2-year cycles from 2011 to 2012. As part of our investigation, we used multivariate logistic regression models to investigate the independent relationship between the Healthy Eating Index and periodontitis. We used odds ratios (OR) with 95% confidence intervals to assess the significance of the connection (95% CI). Results Individuals with a lower total healthy eating index were more likely to have periodontitis. A higher healthy diet index was associated with a lower prevalence of periodontitis (OR = 0.69; 95%CI: 0.49–0.97), according to adjusted multivariate regression models. The restricted cubic spline (RCS) analysis revealed that the non-linear relationship between HEI-2015 and periodontitis was statistically significant and that high HEI-2015 reduced periodontitis prevalence. Conclusion The study’s findings revealed that dietary structure was linked to the prevalence of periodontitis. Patients with a higher Healthy Eating Index were less likely to have periodontitis. There is a need for future prospective longitudinal studies to confirm causality.